2015
DOI: 10.1007/s10801-015-0633-y
|View full text |Cite
|
Sign up to set email alerts
|

Notes on simplicial rook graphs

Abstract: The simplicial rook graph SR(m, n) is the graph of which the vertices are the sequences of nonnegative integers of length m summing to n, where two such sequences are adjacent when they differ in precisely two places. We show that SR(m, n) has integral eigenvalues, and smallest eigenvalue s = max −n, − m 2 , and that this graph has a large part of its spectrum in common with the Johnson graph J (m + n − 1, n). We determine the automorphism group and several other properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In [2] it is shown that the automorphism group of SR(m, n) is S m when n > 3, where S m stands for the permutation group on m elements. Also it is S m × Z 2 when n = 3.…”
Section: Theoremmentioning
confidence: 99%
See 3 more Smart Citations
“…In [2] it is shown that the automorphism group of SR(m, n) is S m when n > 3, where S m stands for the permutation group on m elements. Also it is S m × Z 2 when n = 3.…”
Section: Theoremmentioning
confidence: 99%
“…In [2] it is shown that the automorphism group of SR(m, n) is S m for n > 3, and is S m ×Z 2 for n = 3, where S m stands for the permutation group on m elements. Finally, in this section we study the automorphism group of CSR(m, n).…”
Section: Automorphism Group Of Csr(m N)mentioning
confidence: 99%
See 2 more Smart Citations
“…The eigenvalues of the Johnson graph are known (see [6,10]). Using Loday [25], one can also observe that the graph A n is an induced subgraph of the simplicial rook graph SR n − 2, n−1 2 introduced by Martin and Wagner [28] (see also [5]). We have not been able to use these facts to calculate the eigenvalues of A n .…”
mentioning
confidence: 98%